ZIKI GURU BURA DALAM KEARIFAN LOKAL NUSANTARA DAN TINJAUAN AL-QURAN PADA MASYARAKAT BIMA - Supriatman, Yan Yan (STIT Sunan Giri Bima, 2023)
This research aims to identify Quranic verses that discuss ethics in accordance with the local wisdom values of 'Ziki Guru Bura' within the Bima community. 'Ziki Guru Bura' is a form of poetry known as 'kapatu' among the Bima people. In this context, 'Ziki Guru Bura' has been conveyed with the purpose of enhancing the religious awareness of the community while upholding local wisdom values (within the Bima community). 'Ziki Guru Bura' consists of teachings that serve as a life philosophy and guidance for the community. These teachings are conveyed by an individual who has received the title of 'mursyid' and is considered an exemplary role model for the community in their daily lives. This research employs a qualitative research method with a library research approach to obtain the necessary data. Additionally, it utilizes a thematic interpretation approach to explain the Quranic verses related to the collected data. The results of this research provide insight that behavior originates from the subject and is displayed to others, with others serving as the object of the exhibited behavior. There are three (3) main elements of ideal human behavior in applying the ethical principles of the Quran, as reflected in 'Ziki Guru Bura,' namely: a) ethics towards Allah and His Messenger, b) ethics towards parents, and c) ethics towards teachers.